Critical Writing: Bertold Brechts The Caucasian Chalk Circle (Der Kaukasische Kreidekreis, 1944) - Antonius Herujiyanto (Universitas Sanata Dharma, 2016)
Having read and had discussion on outstanding literary works of European writers, there comes a conviction that the works have indeed played an important role in changing what so-called the course of literary in Europe. They are, indeed, masterpieces which are not simply ones that are done with very great skill. There are, indeed, several aspects to consider before determining what a literary masterpiece isto mention one, its integrity in the light of social conditions and of aesthetics. A better understanding of the works may be achieved, among others, by looking into and situating them in their historical and cultural context. Scrutinizing and analyzing Brechts The Caucasian Chalk Circle is an experience of developing a kind of heightened critical and analytical faculty. It can be poited that the two main characters of the play, Grusha and Azdak, are made use by Brecht to practice his epic theater in general, and his Verfremdungseffekt in particular. They are too estranged for us to be able to accept them as heroes. Brech, however, manages to highlight the vitality of his central characters.